Between integration and repression: Government responses to Islamism in the Maghreb - Isabelle Werenfels (Stiftung Wissenschaft und Politik (SWP), 2005)
Islamist parties have, in Western public opinion, long been seen as an obstacle to democratization in the Arab world. This perspective is strongly qualified, however, by evidence from Arab states in which Islamist parties have been given a chance to participate in political processes.This study compares government strategies of inclusion and repression in Algeria, Morocco, and Tunisia. Two main questions are being addressed: How did these strategies affect the Islamist actors and their strategies, and what do they imply for the politics the EU pursues in the region within the framework of the Barcelona-Process and the European Neighbourhood Policy (ENP), namely the achievement of stability and political reform.The record of the different government strategies suggests that the repression of Islamists - as it is practiced in Tunisia - creates barriers for achieving profound political reform. Conversely, a policy of inclusion of Islamists who support democratic processes - as has been the case in Algerian and in Morocco as of the second half of the 1990s - has led to more pluralist, representative and competitive political systems. Moreover, those Islamist actors that have been given a chance to participate have become more pragmatic and willing to compromise. Integration has been shown to have a stabilizing effect in recent years in Algeria; while in Morocco it has at least had no clearly destabilizing impact. Paradoxically, the interests of the EU in important policy fields, such as constitutional, electoral and economic reforms or fight of corruption, tend to be more congruent with those of the Islamist parties than with those of parts of the ruling elites. As a consequence, a broad participation of Islamists who are ready to subject themselves to democratic rules is desirable from an EU perspective, in particular in view of the reform agenda anchored in the Barcelona-Process and the ENP. (SWP-Research Papers / SWP)
Keywords: 320